Persepsi, Motivasi dan Partisipasi Masyarakat terhadap Keberadaan Ekowisata Mangrove di Kano Maritim Baros Kabupaten Bantul Daerah Istimewa Yogyakarta - Pulungan, Ilham Aulia Anggi; Falah, M. Darul; Rawana (Jurnal Wana Tropika, 2024)
ABSTRACT The concept of sustainable tourism which prioritizes environmental, natural and cultural preservation is known as "ecotourism". Mangroves are a unique ecosystem that has a lot of diversity and beauty. The presence of mangrove ecotourism in the community can have a positive impact and play an important role in ecosystem life. Therefore, community perception, motivation and participation are important factors that determine the existence of ecotourism in an area. Positive perceptions can encourage active community participation in conservation activities, environmental education and ecotourism development. On the other hand, negative perceptions or lack of understanding can become obstacles in environmental conservation efforts. This research was carried out for 3 months in the Kano Maritim Baros Mangrove Ecotourism area, Bantul Regency, Special Region of Yogyakarta. This research aims to see and analyze the perceptions, motivations and participation of communities involved in mangrove ecotourism in Kano Maritim Baros. To process respondent data, this research uses a Likert scale and correlation analysis. The number of respondents in this study was fifty. The results of this study show that the three variables tested for correlation do not have a significant correlation with each other. Apart from that, the perception, motivation and involvement of the community towards the existence of the Kano Maritim Baros mangrove ecotourism is categorized as "Good".